สัญญาอิสติศนาอ และวิธีการประยุกตใชในประเทศกําลังพัฒนา = The developmental role of Istina’ Contract in Developing Countries in arabic = عقد الاستصناع ودوره التنموي في الدول النامية - Laeba, Muhammad (Fatoni University, 2014)
The research aims to study the contract of istisna’ and the methods of applying it in Islamic banks. The study will also shade light on the Islamic Banks’ role in develeoping of the manufacturing sectors by using contract of istisna’ as a mode of financing, especially in the developing countries which still need to be politically, socially and economically developed. The study also contains the ways in wich the profits are to be distributed.The potential fields in which the contract of istisna’ may be applied were also discused. Inductive and analytical methods have been adopted in this research. In addition, the study also stated that innovating and developing of the modern and shari’ah compliant products and financial tools is necessary in order to differentiate them from conventional one. Istisna’i contract is considered as one of the significant mode of financing used by Islamic Banks. The paper also disclosed that colonization, low income and weak production are amongst the causes that make some countries to be counted as underdeveloped countries. Finally, the research concludes that using Istisna’i contract in the infrastructure’s projects, real estate and natural productive may help in the development of developing countries.